2016
DOI: 10.1007/s00394-016-1346-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of buffalo casein-derived novel bioactive peptides on osteoblast differentiation

Abstract: All peptides enhanced osteoblast differentiation along with the positive controls. These results hold an immense scope to use peptides as preventive measure for reducing incidence of osteoporosis. These peptides can also be used as drugs and can be utilized as functional ingredients in functional foods preparation for osteoporosis therapy, but in vivo studies are required for further confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Reportedly, peptide 9 is detected in casein hydrolysates involved in nervous system development and antioxidant effects [ 36 , 37 ]. Peptide 12 is present in casein hydrolysates known to have antioxidant, anti-hypertension, and osteoblast proliferation/differentiation effects [ 38 , 39 , 40 ]. Although the antioxidant effect is commonly observed, other peptides listed in the table (peptides 1 and 5) are also present in antioxidant casein hydrolysates, indicating that their molecular mechanisms need to be revealed [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, peptide 9 is detected in casein hydrolysates involved in nervous system development and antioxidant effects [ 36 , 37 ]. Peptide 12 is present in casein hydrolysates known to have antioxidant, anti-hypertension, and osteoblast proliferation/differentiation effects [ 38 , 39 , 40 ]. Although the antioxidant effect is commonly observed, other peptides listed in the table (peptides 1 and 5) are also present in antioxidant casein hydrolysates, indicating that their molecular mechanisms need to be revealed [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This expression gradually decreased over time up to seven days. Alkaline phosphatase is an essential early differentiation marker released by osteoblasts and/or odontoblasts in the initial stage of calcified tissue formation [25,31,32], during the initiation of mineralization to allow the formation of hydroxyapatite [31,32]. It was reported that alkaline phosphatase exhibited its maximum expression by differentiated osteoblasts within the first few days and then gradually declined on days seven and 14 [33].…”
Section: Discussionmentioning
confidence: 99%
“…Bone sialoprotein and osteocalcin are major noncollagenous proteins expressed by fully differentiated osteoblasts and/or odontoblasts in relation to late-stage calcified tissue formation, and the regulation of the formation and growth of hydroxyapatite crystal of bone and cementum mineralization [31,35,38]. Bone sialoprotein is a marker that indicates an increased mineralization level of osteoblasts [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, fermented dairy foods are often attributed to the release of bioactive peptides from milk proteins by the microbial degradation using proteinases in the cell wall of lactic acid bacteria (Otag and Hayta 2013 and Martinez Villaluenga et al 2017). The most significant subgroup of bioactive peptides present in fermented dairy foods include anti-hypertensive (Beltran-Barrientos et al 2016), osteogenic (Reddi et al 2018), anti-oxidative and anti-inflammatory (Sowmya et al 2018 and, mineral binding peptides (Mann et al 2019) and the angiotensin-1-converting enzyme (ACE) inhibitor peptides (Nejati et al2013). Exo-polysaccharides, composed of repeating monoor oligosaccharide subunits bound by various glycosidic linkages (Fanning et al 2012), are also produced by various microorganisms during fermentation (Deepak et al 2016).…”
Section: Bioactive Compounds Released During Dairy Fermentation With mentioning
confidence: 99%